2020
DOI: 10.1155/2020/9671871
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Dispersion of As, Cd, Pb, and Zn in Farmland Soils near Abandoned Mine Tailings: Field Observation Results in South Korea

Abstract: We investigated the characteristics of metal(loid) transport and dispersion in agricultural soils near an abandoned metal mine. Topsoil samples were collected from 162 sampling sites in the study area, including 1 in the mine tailing dumps, to analyze the total concentrations of As, Pb, Cd, and Zn. Subsequently, the metal(loid) transport and dispersion characteristics were investigated using geographic information system (GIS) technology. The results of this study clearly demonstrated the variation in the disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…In particular, the total concentration of Pb was found to be more than 250 times the national limit of 200 mg/kg. (Yun et al, 2020).The same study was carried out in the wetlands Liupanshui Minghu which is an industrial and mining area, by measuring the concentrations of heavy metals lead(Pb), zinc(Zn),copper(Cu) in surface deposits, and the results of the average concentrations were (197), ( 222), (59,1), (68, 6), (4,67) mg/kg, respectively, it is an area of environmental risk. (Yu et al, 2021).There is a study on the concentrations of abandoned mine tailings, in 2006 in the region of High Moulaya, which is the region of the mining industry in eastern Morocco.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the total concentration of Pb was found to be more than 250 times the national limit of 200 mg/kg. (Yun et al, 2020).The same study was carried out in the wetlands Liupanshui Minghu which is an industrial and mining area, by measuring the concentrations of heavy metals lead(Pb), zinc(Zn),copper(Cu) in surface deposits, and the results of the average concentrations were (197), ( 222), (59,1), (68, 6), (4,67) mg/kg, respectively, it is an area of environmental risk. (Yu et al, 2021).There is a study on the concentrations of abandoned mine tailings, in 2006 in the region of High Moulaya, which is the region of the mining industry in eastern Morocco.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, exposure assessment through cAs, rather than UAL AAS , is recommended for vulnerable areas where seafood consumption and human exposure risks of iAs are high. In particular, recently, a study was published that found a high possibility of As contamination on agricultural soils in abandoned metal mines in Korea [7]. This study assessed the interchangeability of cAs based on UAL AAS and established the unreliability of the estimated exponential and nonlinear second-order polynomial models.…”
Section: Discussionmentioning
confidence: 99%
“…Food is the second leading source of As intake [6]. Exposure might result from the consumption of crops grown in As-contaminated soils and dust inhalation in polluted areas such as mines [1,7]. Occupational exposure can occur through the inhalation of dust or aerosols with high As levels [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, for each sampling plot, three individual grabs of soil were collected from randomly selected locations within the plot, and then mixed to form a composite sample. Soils were collected in the upper layer (0–30 cm) known to be the habitat of biological factors influencing plant growth [ 36 ], and which is commonly used for soil sampling in disturbed environment including agricultural lands and mine-generated wastelands [ 37 , 38 , 39 ].…”
Section: Methodsmentioning
confidence: 99%